Prevention of an additional surgery for regional lymphadenectomy in melanoma: rapid intraoperative immunostaining of sentinel lymph node imprint smears - Campbell Bruce H; Walker Alonzo; Neuberg Marcelle; Komorowski Richard; Shidham Vinod B; Chang Chung-Che; Dzwierzynski William W (BMC, 2006)
Abstract Background Sentinel lymph node (SLN) biopsy is performed at many institutions and is considered a standard of care in the management of cutaneous melanoma. The discriminatory immunostaining pattern with the 'MCW Melanoma Cocktail' (a mixture of MART-1 {1:500}, Melan- A {1:100}, and Tyrosinase {1:50} monoclonal antibodies) allows intraoperative immunocytochemical evaluation of imprint smears of SLNs for melanoma metastases. Cohesive cells of benign capsular melanocytic nevi that were also immunoreactive with the cocktail do not exfoliate easily for imprint smear detection. Methods We prospectively evaluated 73 lymph nodes (70 SLN & 3 non-SLN) from 41 cases (mean 1.8, 1 to 4 SLNs/case) of cutaneous melanoma using a rapid 17-minute immunostaining previously published protocol. The results were compared with permanent sections also immunostained with 'the cocktail'. Results 19.5%, 8/41 cases (12%, 9/73 lymph nodes) were positive for melanoma metastases on permanent sections immunostained with the 'MCW melanoma cocktail'. Melanoma metastases in 87.5% (7/8) of these cases were also detected in rapidly immunostained imprint smears, with 100% specificity and 90% sensitivity. None of the 7 SLNs from 7 cases with capsular nevi showed false positive results. Conclusion Melanoma metastases could be detected in imprint smears immunostained with 'MCW Melanoma Cocktail' utilizing a rapid intraoperative protocol. The cohesive cells of the capsular nevi do not readily exfoliate and do not lead to false positive interpretation. In a majority of positive cases, a regional lymphadenectomy could have been completed during the same surgery for SLN biopsy and wide excision of primary melanoma site, potentially eliminating the need for an additional surgery.